Osteoprotegerin Polymorphisms in a Mexican Population with Rheumatoid Arthritis and Generalized Osteoporosis: A Preliminary Report - Maria Guadalupe Zavala-Cerna; Maria Cristina Moran-Moguel; Jesus Alejandro Cornejo-Toledo; Norma Guadalupe Gonzalez-Montoya; Jose Sanchez-Corona; Mario Salazar-Paramo; Arnulfo Hernan Nava-Zavala; Erika Anita Aguilar-Chavez; Miriam Fabiola Alcaraz-Lopez; Alicia Guadalupe Gonzalez-Sanchez; Laura Gonzalez-Lopez; Jorge Ivan Gamez-Nava (Journal of Immunology Research)
Bone disease in rheumatoid arthritis (RA) is a complex phenomenon where genetic risk factors have been partially evaluated. The system formed by receptor activator for nuclear factor-κB (RANK), receptor activator for nuclear factor-κB ligand (RANKL), and osteoprotegerin (OPG): RANK/RANKL/OPG is a crucial molecular pathway for coupling between osteoblasts and osteoclasts, since OPG is able to inhibit osteoclast differentiation and activation. We aim to evaluate the association between SNPs C950T (rs2073617), C209T (rs3134069), T245G (rs3134070) in the TNFRSF11B (OPG) gene, and osteoporosis in RA. We included 81 women with RA and 52 healthy subjects in a cross-sectional study, genotyped them, and measured bone mineral density (BMD) at the lumbar spine and the femoral neck. Mean age in RA was 50±12 with disease duration of 12±8 years. According to BMD results, 23 (33.3%) were normal and 46 (66.7%) had osteopenia/osteoporosis. We found a higher prevalence of C allele for C950T SNP in RA. Polymorphisms C209T and T245G did not reach statistical significance in allele distribution. Further studies including patients from other regions of Latin America with a multicenter design to increase the sample size are required to confirm our findings and elucidate if C950T SNP could be associated with osteoporosis in RA.